2004
DOI: 10.3177/jnsv.50.78
|View full text |Cite
|
Sign up to set email alerts
|

Low Dose-Ethanol Modulates Toxic Effect of Iron-Overloading in the Liver

Abstract: SummaryThe oxidant properties of iron-overload and simultaneous ethanol consump tion have received much interest, due to evidence reporting from hereditary hemochroma tosis (HC). The full form of this disease is often associated with chronic alcoholism . An additive effect of toxicity of iron and ethanol was assumed . In this study, we examined nutri tively iron-loaded Wistar rats (n=59) (TMH-Ferrocene) additionally fed with ethanol up to 8% in drinking water for 36wk. Methods: By reverse-phase HPLC we measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This was then dissolved in 400 μl methanol solution, after which 100 μl of the solution was analysed by high-performance lipid chromatography (HPLC). In the case of vitamin C, the diluted filtrate obtained as above was used for direct analysis as described previously (Beutelspacher et al 2004). …”
Section: Reagents and Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was then dissolved in 400 μl methanol solution, after which 100 μl of the solution was analysed by high-performance lipid chromatography (HPLC). In the case of vitamin C, the diluted filtrate obtained as above was used for direct analysis as described previously (Beutelspacher et al 2004). …”
Section: Reagents and Cellsmentioning
confidence: 99%
“…Here, using iron-mediated lipid-peroxidation as an in vitro model system (Beutelspacher et al 2004), we show the direct toxicity of free radicals to CECs and the influence of anti-oxidative vitamins on CECs survival. In an attempt to attenuate cell death caused by oxidative stress induced by iron-mediated lipid-peroxidation, vitamins A, C and E have been administered to CECs undergoing apoptosis in response to sustained oxidative damage and their effect on the apoptotic rate and activation of caspase-3, an apoptosis executer enzyme, has been assessed.…”
Section: Introductionmentioning
confidence: 98%
“…An in vivo study, which produced conflicting results, was conducted on 59 mice [ 100 ] and reported a lower bioavailability of vitamins (especially vitamin E) in all animals exposed to an iron-containing diet and alcohol consumption (at doses of 2%, 5%, and 8%). A significant increase in lipid peroxidation activity was found in all animals consuming alcohol, an iron-rich diet, or both.…”
Section: Hemochromatosismentioning
confidence: 99%